Structural and mechanical changes by adding graphene to C/C composites. Issue 20 (15th October 2022) - Wang, Yafeng; Xiao, Lijun; Zeng, Chen; Tong, Kai; Fan, Zheqiong; Zeng, Guang; Wang, Xiaodong; Su, Zhean; Zhang, Mingyu; Huang, Qizhong
Abstract: The structure and mechanical properties of C/C composites prepared by isothermal isobaric chemical vapor infiltration (ICVI) were investigated to evaluate the influence of introducing graphene. The results indicated that adding graphene significantly improved the texture of pyrocarbon. The pure pyrocarbon was primarily composed of smooth laminar (SL) structure, while the pyrocarbon in composites containing graphene was dominated by regenerative laminar (ReL) structure. Furthermore, with 0.66 wt% addition of graphene, the compression performance of the C/C composites was prominently improved by 70.9%, increasing from 107.37 MPa to 183.45 MPa, while the bending strength of the C/C composites was slightly decreased. The variation of mechanical properties was attributed to graphene-induced weakening of interfacial bonding and improved texture of pyrocarbon, resulting in a more compact arrangement of carbon layers and better integrity of the matrix. This work contributed to the understanding of the improved properties and structure of C/C composites with graphene addition.